Random X chromosome inactivation in female Charcot-Marie-Tooth disease type X1: insights from sural nerve biopsy analysis - Bekircan-Kurt, Can Ebru; Aksu-Menges, Evrim; Kumtepe, Eray Taha; Durmaz, Ceren Damla; Terzi, Yunus Kasim; Ergul-Ulger, Zeynep; Temucin, Çagri Mesut; Erdem-Ozdamar, Sevim; Tan, Ersin; Balci-Hayta, Burcu (BMC neurology, 2025)
Background X-linked Charcot-Marie-Tooth disease type 1 (CMTX1) is a hereditary neuropathy caused by mutations in the GJB1 gene encoding Connexin 32 (Cx32). Despite its X-linked dominant inheritance, it has been suggested that the variable phenotypic expression of the disease in females may be due to skewed X chromosome inactivation (XCI) in Schwann cells. This pilot study aimed to examine the XCI patterns in archived sural nerve biopsies of female patients diagnosed with CMTX1 for the first time in the literature. Methods Two unrelated female CMTX1 patients, initially misdiagnosed with chronic inflammatory demyelinating polyneuropathy (CIDP), with motor conduction blocks were included. GJB1 mutations were identified using whole-exome sequencing (WES). XCI patterns were analyzed using the human androgen receptor (HUMARA) assay on archived fresh-frozen sural nerve biopsy samples performed prior the genetic diagnosis and compared with age-matched vasculitic neuropathy controls. Results The GJB1 c.379 A > C mutation was identified in both CMTX1 patients. XCI analysis revealed a random XCI pattern in affected nerve tissues, with no significant differences between patients and controls. Conclusion Contrary to previous hypotheses, our findings suggest that XCI does not contribute to phenotypic variability in female CMTX1 patients. These results highlight the complexity of CMTX1 pathophysiology and highlight the need for further studies on alternative mechanisms regulating disease severity in females. Keywords: X-linked Charcot-Marie-Tooth disease type 1, Phenotypic variability, X chromosome inactivation, Sural nerve biopsy, HUMARA assay